ANALISA PENGARUH PERCEIVED SUPERVISOR SUPPORT DAN JOB INSECURITY TERHADAP TURNOVER INTENTION DENGAN EMPLOYEE ENGAGEMENT SEBAGAI VARIABEL INTERVENING - Heri Cahyono; Rahayu Puji Suci; Nasharuddin Mas (Jurnal Pendidikan Dasar dan Sosial Humaniora, 2023)
This study aims to obtain empirical evidence of the ability of perceived supervisor support and job insecurity to reduce turnover intention, either directly or through employee engagement mediation. This type of research is quantitative using the SEM-SmartPLS method. Data was obtained through questionnaires which were distributed to 71 contractor/TKJP employees PT PHM’s Senipah field (Pertamina Hulu Mahakam). The results obtained indicate the ability of perceived supervisor support to reduce turnover intention, but this is not the case with job insecurity, which is unable to strongly influence turnover intention. Both perceived supervisor support and job insecurity can affect employee engagement. Employee engagement is not able to mediate strongly the effect of perceived supervisor support on turnover intention. However, employee engagement is able to mediate strongly the effect of job insecurity on the turnover intention of contractor/TKJP employees in the PT PHM Senipah field (Pertamina Hulu Mahakam)